Social Bricolage: Theorizing Social Value Creation in Social Enterprises - Di Domenico, MariaLaura; Haugh, Helen; Tracey, Paul (Entrepreneurship Theory and Practice, 2010)
Current theorizations of bricolage in entrepreneurship studies require refinement and development to be used as a theoretical framework for social entrepreneurship. Our analysis traces bricolage's conceptual underpinnings from various disciplines, identifying its key constructs as making do, a refusal to be constrained by limitations, and improvisation. Although these characteristics appear to epitomize the process of creating social enterprises, our research identifies three further constructs associated with social entrepreneurship: social value creation, stakeholder participation, and persuasion. Using data from a qualitative study of eight U.K. social enterprises, we apply the bricolage concept to social entrepreneurial action and propose an extended theoretical framework of social bricolage.